Pengaruh Pendapatan Asli Daerah dan Transfer ke Daerah Dana Desa Terhadap Kemandirian Keuangan Daerah Kabupaten/Kota di Provinsi Riau The Effect of Regional Original Income and Transfers to Village Fund Areas on Regency/City Regional Financial Independenc - Shalshyabilla, Bulan; Azzakhusna, Famita; Anan, Edy; Lanaula, Rima (Sekolah Tinggi Ilmu Ekonomi Bisnis dan Perbankan, 2023)
This research was conducted with the aim of analyzing the effect of regional original income and transfers to regions and village funds on the financial independence of districts/cities in Riau Province from 2018-2022. The dependent variable used in this study is Regional Financial Independence, then the independent variables are Regional Original Income, Transfers to Regions and Village Funds. This research uses a descriptive method with panel data regression analysis. The data used is secondary data obtained from the Ministry of Finance's website from 2018 to 2022, as many as 12 districts/cities in Riau Province. The analysis tool used is the software program Eviews 10. The results of this study indicate that Regional Original Income has a negative and significant effect on Regional Financial Independence, Transfers to Regions and Village Funds have a positive and significant effect on Regional Financial Independence. From the results of the F test, it shows that Regional Original Income, Transfers to Regions and Village Funds together have a positive and significant effect on Regional Financial Independence.